THEME: COMPARATIVE ANALYSIS OF THE POLITICAL SYSTEMS OF THE UNITED KINGDOM AND UZBEKISTAN - Muhammadyunusova Marhabo Qodirjon qizi, (TADQIQOTLAR, 2025)
Abstract This  article  analyzes  the  political  systems  of  the  United  Kingdom  and  the Republic of Uzbekistan from both historical and functional perspectives. It compares the structures of government, legislative institutions, electoral systems, and political parties in both countries. The study highlights the similarities and distinctive features of  each  system  and  provides  useful  insights  for students, researchers, and  political analysts.